Comparative histopathology of climbing perch, Anabas testudineus challenged with Aeromonas veronii via IM and IP routes (Journal of Advanced Veterinary and Animal Research, 2026)
Objective: The focal purpose of this investigation was to contrast the pathological changes from different histological observations of Anabas testudineus artificially infected with Aeromonas veronii. Materials and Methods: Intramuscular (IM) and intraperitoneal (IP) injection routes were used to challenge fish with three different bacterial concentrations, including 2.1 × 105 , 2.1 × 10⁵, and 2.1 × 10⁴ cfu ml⁻¹ of bacteria to investigate the effects of various loads of A. veronii on the histopathological alterations in the skin-muscle, liver, and intestine of A. testudineus during 13 days of post-challenge test. Two replicates (n = 10) were used for each of the IM and IP groups, corresponding to the three aforementioned bacterial loads, in the challenge test for this study. Results: The highest bacterial challenge (2.1 × 10⁴ cfu ml⁻¹) groups from both IP and IM produced some prominent clinical signs, e.g., red spots, ulcers, and lesions on the body surface, and highest cumulative mortality (IP = 50% and IM = 40%) compared to the control groups having no pathological signs in all organs. Histopathological alterations observed under the light microscope revealed significant pathologies (e.g., vacuolation and necrosis) in all organs studied, particularly at the highest bacterial loads, compared to the other challenges and control groups. It suggests that varied bacterial loads can produce different types of pathology in various fish organs. Conclusion: Aeromonas veronii can cause mortality and remarkable pathological changes in different organs of A. testudineus. Findings from experimental infections can be used as an effective tool to predict the virulence of pathogens and to develop advanced prevention and health management strategies in aquaculture.J. Adv. Vet. Anim. Res., 12(4): 1275–1285, December 2025http://doi.org/10.5455/javar.2025.l988